If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -3m + -8 = 26 Reorder the terms: -8 + 2m + -3m = 26 Combine like terms: 2m + -3m = -1m -8 + -1m = 26 Solving -8 + -1m = 26 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1m = 26 + 8 Combine like terms: -8 + 8 = 0 0 + -1m = 26 + 8 -1m = 26 + 8 Combine like terms: 26 + 8 = 34 -1m = 34 Divide each side by '-1'. m = -34 Simplifying m = -34
| Px+Q=X+1 | | 2x+4(2x+8)=10x+32 | | 1+8x^2+x^4= | | 90=(4x+12)+(6x+8) | | 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a | | (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 | | 3d+2=12 | | X*.0147=(X-67) | | 11=3u-13 | | 11=3u+13 | | (x-67)=x*1.47 | | 6d+(5.5)=2d-(6.5) | | 6d+5.5=2d-(6.5) | | 6d+5.5=2d-6.5 | | 17x+3=17x | | -33*1/5 |